Development of an Online Project-Based Learning Assessment Instrument for Vocational Education Students - Islami, Syaiful; Ambiyar, Ambiyar; Sukardi, Sukardi; Zaus, Mahesi Agni; Zaus, Anggi Agni (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Objectives from the study This is an instrument for reliable online project-based learning assessment for vocational education students. Study This uses 10 procedures for the non-ttest instrument developed by Mardapi. The population study covers the whole Electrical Engineering Education student’s year at the First Faculty of Engineering, Universitas Negeri Padang. The sample consists of the 250 students selected through two stages: the trial stage, which uses the cluster random sampling method, and the stage measurement, which uses the simple random sampling method. Data analysis was performed using validity tests using the Aiken index as well as validity and reliability tests. Findings study These are (1) instruments. The assessment of project-based learning online consists of 30 valid and reliable items, so it can be used by lecturers. (2) Ability to measure cognitive, affective, and psychomotor skills in the learning process Cognitive, affective, and psychomotor vocational education students tend Good.